1989
DOI: 10.1177/001872088903100104
|View full text |Cite
|
Sign up to set email alerts
|

Processing Demands, Effort, and Individual Differences in Four Different Vigilance Tasks

Abstract: In an attempt to specify the limiting conditions of the taxonomy of vigilance tasks, four tasks differing in memory load and in stimuli employed (sensory or cognitive) were compared. Electrodermal activity and subjective measures were used to determine the investment of effort. The data show that vigilance level and vigilance decrement dissociate. The level seems to relate to effort demand and investment; the decrement seems to be task driven, determined mainly by the type of stimuli used. Tasks employing unfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…The way of searching the literature, the ordering of the studies, the inclusion of particular test characteristics purportedly affecting study outcomes, the measures of performance considered etc., are in essence the same as described in an earlier review of the effects of benzodiazepines (Koelega 1989).…”
Section: Methodsmentioning
confidence: 90%
See 4 more Smart Citations
“…The way of searching the literature, the ordering of the studies, the inclusion of particular test characteristics purportedly affecting study outcomes, the measures of performance considered etc., are in essence the same as described in an earlier review of the effects of benzodiazepines (Koelega 1989).…”
Section: Methodsmentioning
confidence: 90%
“…The conclusion that vigilance tasks rank highest in sensitivity to stimulant drug effects was also reached earlier (Koelega 1989) with respect to the effects of (sedative) benzodiazepines, albeit hedged by the finding that in patients, effects were tess often noted than in young volunteers. Lieberman et al (1987b) reported that as little as 32 mg caffeine, typical of the dose found in a single serving of cola beverage, and less than that found in a single cup of coffee, significantly improved auditory vigilance.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations